STRATEGI KOMUNIKASI PEMASARAN TERPADU JASA FOTOGRAFI DAILY PHOTOWORKS - Stepanus, Kelvin; Hilda Yunita Wono (Jurnal Spektrum Komunikasi, 2024)
The Covid-19 pandemic, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has created profound global impacts on a scale comparable to the 1918 flu pandemic. Originating in Wuhan, China, in late 2019, the pandemic rapidly spread, leading the World Health Organization (WHO) to declare it a pandemic on December 31, 2019. In Indonesia, the first confirmed case was reported on March 2, 2020, triggering the implementation of Large-Scale Social Restrictions (PSBB) policies to control the virus's spread. The pandemic's impact has permeated various sectors, including the photography services sector. Despite the negative effects brought by the pandemic, photography businesses have sought adaptation by relying on technology, particularly the internet. This technology has become a primary determinant in navigating market changes and sustaining business operations. Daily Photoworks is one of the businesses that have harnessed technology. Some of the strategies they have employed include collaborating with event organizers and local influencers, as well as utilizing social media. These strategies have resulted in an increase in their client base. This increase during the period from 2018 to 2023 reflects the effectiveness of their integrated marketing communication strategies. Amidst these changes, Integrated Marketing Communication (IMC) strategies have become a key element in building brand awareness and maintaining customer loyalty. This study employs structured interviews and analysis using Nvivo 14 to uncover the successful integrated marketing communication strategies in addressing pandemic challenges and their impact on the photography business.